Gamblified digital product offerings: an experimental study of loot box menu designs - Martin Adam; Konstantin Roethke; Alexander Benlian (Electronic Markets, 2021)
To augment traditional monetization strategies, digital platform providers increasingly draw on gamblification (i.e., the use of gambling design elements). By means of gambling design elements (e.g., lottery tickets, scratch cards, loot boxes), platform providers do not only entertain users but also incentivize them to purchase digital products. Yet, despite the increasing prevalence of gamblified digital platforms, little is known about how gamblification influences user purchase behaviors. Drawing on prospect theory, we investigate gamblification in the form of loot box menu designs and the associated effects of uncertainty, loss experience and behavioral control on user purchase behavior. Specifically, we conducted a contest-based online experiment with 159 participants, finding that platform providers can profit from offering loot boxes with certain (vs. uncertain) rewards in loot box menus. Furthermore, this effect intensifies when participants previously experienced a loss and decreases when they perceive to have more control over the result. Thus, our findings provide theoretical and practical insights for a better understanding of gamblification in general and of loot box menu designs for enhancing digital business models in particular.
Keywords: C91; D91; M38; 620; Gamblification; Gambling; Gamification; Digital business models; Loot box; Prospect theory